An exploration of the New Zealand use of technology to facilitate logistics - Wood, Lincoln; Wood, A.; Reiners, Torsten; Duong, N.; Wang, X. (ACIS, 2014)
This paper summarises a survey to understand the current state of adoption and use of Logistics Technology, encompassing both information technology and materials handling technologies, in New Zealand. An exploratory survey was distributed to appropriate firms. We present descriptive statistics relating to the reasons for adopting the technologies, the drivers for adoption, metrics used to establish whether the technology has increased value, and the education and training provided relating to these technologies. We find that inter-firm technology and measurement is uncommon, Followers are still likely to be implementing transactional and internally integrative technologies, Leaders are more likely to be planning to implement materials handling technologies and are more sophisticated in their educational and training programmes.